Frequency voltage stability in network-independent hybrid micro grids with V2G electric vehicles and reactive power compensators - Sajed Sanginabadi , Javad Olamaei, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Today, due to technical and environmental issues as well as economic issues, the tendency towards smart grids and the creation of microgrids has received more and more attention. In terms of network connectivity, microgrids can be classified into two categories: connected and disconnected from the network. When connected to the network, control issues are not very visible. When the microgrid goes to the island state, the discussion of power balance, maintaining the desired frequency and voltage stability is one of the important and key issues of a microgrid. For this reason, microgrid stability requires a controller that can keep these parameters at the desired level and prevent the microgrid from collapsing. Another type of microgrid classification is based on the type of power, ie AC and DC powers or a combination of The two call this type of combination a hybrid microgrid. In this paper, a method based on the use of distributed generation control method based on active power distribution and frequency recovery is used. The proposed controller is located in the frequency control loop, and by applying a control signal to the sources, the frequency fluctuations following the power changes in the microgrid are reduced. With the advent of compensators, the voltage and frequency stability results produced by the controller were improved, and the outputs from the SVC were far better than those from STATCOM. The presence of the vehicle in the microgrid causes a frequency change that the proposed controller provides a good output of the frequency.